ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN JOB ORDER COSTING UNTUK OPTIMALISASI PENENTUAN HARGA (STUDI KASUS CV GLOBALINDO PERKASA ENGINEERING) - R Taufik Hidayat,; Rani Priani, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to determine the method used by the company to calculate the cost of production and compare it with the calculation of the job order costing method and to determine the role of the Job Order Costing method in assigning costs accurately and efficiently.The data collection method used is the method of field studies interviews), literature studies, documentation. This research uses research techniques by going directly to the production site, documentation, and literature studies that are used to strengthen and deepen the study of the object under study. The data analysis method used is descriptive test analysis technique, descriptive test is a way of formulating or interpreting existing data so as to be able to provide a clear picture through collecting, compiling, and analyzing data, so that a general description of the company's production activities can be known. The results show that CV Globalindo Perkasa Engineering has not used the calculation of the cost of production and has not classified its costs. By using the calculation of the cost of production using the job order costing method, the resulting cost of goods manufactured is Rp. 1,112,912.34 and ends at a selling price of Rp. 1,391,140. the calculation of the cost of production using the job order costing method is smaller than the calculation of CV Globalindo Perkasa Engineering